Improving provision of effective psychological care for LGB persons: client perceptions of diversity competences of clinical psychologists and psychotherapists - Moleiro, C.; Pinto, N. (Psicologia, 2012)
While clinicians are becoming increasingly aware of the need to be competent in terms of cultural and individual diversity, European professional associations have made little progress in establishing guidelines and standards of care, practice and training – contrary to their North American counterparts. The purpose of the present paper is to contribute to the recognition of clinician diversity competences as viewed by LGB clients. It further aims to describe the perceptions that these clients have of these competences, in terms of their dimensions, illustrations, and their presence/absence in actual clinical practice. The present study utilizes a qualitative methodological approach, involving the use of 3 focus groups with 15 LGB persons. A focus group plan was developed and focus groups were conducted in a non?clinical setting, after recruitment through LGBT associations. Content analysis was conducted on the transcripts of the focus groups. Results included similar proportions of units of analysis in the dimensions of awareness (31%), knowledge (37%) and skills (32%). Clinician LGB awareness, however, was evaluated as more central in relation to the other two dimensions; and, overall, perceptions of competences actually present in clinical practice only made up 6% of units of analysis. The results argue for the foundational role of clinicians? LGB diversity competences when working with sexually diverse individuals.